Ultrasound Image Optimization (“Knobology”): B-Mode - Zander, David; Hüske, Sebastian; Hoffmann, Beatrice; Cui, Xin-Wu; Dong, Yi; Lim, Adrian; Jenssen, Christian; Löwe, Axel; Koch, Jonas B.H.; Dietrich, Christoph F. (Ultrasound International Open, 2020)
Ultrasound is a ubiquitous and indispensable diagnostic and therapeutic tool in medicine. Due to modern equipment and automatic image optimization, the introduction of ultrasound imaging currently requires only little technical and physical knowledge. However, in-depth knowledge of the device functions and underlying mechanisms is essential for optimal image adjustment and documentation. From a medical as well as an aesthetic point of view, the goal should always be to achieve the best possible image quality. The first part of this article provides an overview of the handling of ultrasound systems, fundamental adjustments, and their optimization in B-mode ultrasound.
Keywords: ultrasound; Methods & techniques; B-mode; resolution; image quality; image optimization